2021
DOI: 10.1055/s-0041-1728830
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Rotavirus Genotypes among Children Younger than 5 Years with Acute Gastroenteritis in Zaria, Northwestern Nigeria

Abstract: Objective This study aimed to determine the circulating rotavirus genotypes among children 0 to 59 months with acute gastroenteritis in Zaria, Northwestern Nigeria. Methods A cross-sectional hospital-based study was performed from November 2015 to April 2017 on 415 stool samples of children 0 to 59 months with acute gastroenteritis presenting at the pediatric clinics in five selected health care facilities in Zaria, Northwestern Nigeria. The stool samples were tested for group A rotavirus antigen by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although breast feeding is generally thought to at least reduce the severity of the disease, its specific role in preventing RV diarrhea is controversial [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The WHO has recommended continuing breastfeeding during RV diarrhea [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although breast feeding is generally thought to at least reduce the severity of the disease, its specific role in preventing RV diarrhea is controversial [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The WHO has recommended continuing breastfeeding during RV diarrhea [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the severity and duration of the disease in breastfed children are low [ 25 ]. Linhares A et al [ 28 ] reported that children aged 0–3 years in Brazil had no evidence of protection against clinical RV by breastfeeding. Differences in study designs and the age of the populations studied have led to differences in study results regarding the effect of breastfeeding on RV diarrhea.…”
Section: Discussionmentioning
confidence: 99%